Effect of intermittent theta burst stimulation on upper limb function in stroke patients: a systematic review and meta-analysis - Lu, Junyue; Huang, Jiahao; Ye, Anqi; Xie, Chen; Bu, Pan; Kang, Jiliang; Hu, Jiaxuan; Wen, Youliang; Huang, Haoyuan (Frontiers in Neurology, 2024)
Background：Stroke is a serious health issue that affects individuals, families, and society. Particularly, the upper limb dysfunction caused by stroke significantly reduces the quality of life for patients and may lead to psychological issues. Current treatment modalities are not fully effective in helping patients regain upper limb motor function to optimal levels. Therefore, there is an urgent need to explore new rehabilitation methods to address this issue.The purpose of this meta-analysis and systematic review is to explore the effects of intermittent theta burst stimulation (iTBS) on upper limb function in stroke patients.Methods: We searched PubMed, Cochrane Library, Embase, Web of Science, and PEDro as of April 8, 2024. Retrieved a total of 100 articles. Standardized mean differences (SMDs) and 95% confidence intervals (CI) were calculated.The study included a total of 9 trials and involved 224 patients. The results demonstrate that compared to the control group, iTBS therapy significantly improved Fugl-Meyer assessment-upper extremity (FMA-UE) scores (SMD =0.88; 95% CI = 0.11 1.66; P=0.03, I 2 = 84%), Action Research Arm Test (ARAT) scores (SMD =0.83; 95% CI = 0.16 1.50; P = 0.02, I 2 = 57%), and Barthel Index (BI) scores (SMD =0.93; 95% CI = 0.53 1.32; P < 0.0001, I 2 = 0%)in stroke patients.The comprehensive evidence suggests that iTBS has superior effects in improving upper limb function and activities of daily living in stroke patients.